The Protection of Fundamental Rights in the Jurisprudence of the CJEU and the Charter – Twelve Years On - Szerencsés, Anna Réka (Pécs journal of international and European law, 2021)
While national governments remain ambivalent about the EU’s role in relation to human rights matters within the EU, the CJEU has taken a broad view of what falls within the scope of EU law for the purposes of Article 51 (field of application) of the Charter of Fundamental Rights of the EU. Mainly, in the event of conflict, it has asserted the primacy of EU law and of the Charter over national constitutional law. The Article therefore studies the development of human rights protec- tion and the role of the Charter, Member State law, and international organizations in the matter of fundamental rights and freedoms. The paper considers the future of the CJEU’s protection policy and provides a conclusion of the analysed issues at hand.